A Minskyan road to financial reform - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
In the aftermath of the global financial collapse that began in 2007, governments around the world have responded with reform. The outlines of Basel III have been announced, although some have already dismissed its reform agenda as being too little (and too late!). Like the proposed reforms in the United States, it is argued, Basel III would not have prevented the financial crisis even if it had been in place. The problem is that the architects of reform are working around the edges, taking current bank activities as somehow appropriate and trying to eliminate only the worst excesses of the 2000s. Hyman Minsky would not be impressed. Before we can reform the financial system, we need to understand what the financial system does - or, better, what it should do. To put it as simply as possible, Minsky always insisted that the proper role of the financial system is to promote the capital development of the economy. By this he did not simply mean that banks should finance investment in physical capital. Rather, he was concerned with creating a financial structure that would be conducive to economic development to improve living standards, broadly defined. In this paper, we first examine Minsky's general proposals for reform of the economy - how to restore stable growth that promotes job creation and rising living standards. We then turn to his proposals for financial reform. We will focus on his writing in the early 1990s, when he was engaged in a project at the Levy Economics Institute on reconstituting the financial system (Minsky 1992a, 1992b, 1993, 1996). As part of that project, he offered his insights on the fundamental functions of a financial system. These thoughts lead quite naturally to a critique of the financial practices that precipitated the global financial crisis, and offer a path toward thorough-going reform.
Keywords: B22; B25; B26; B52; E02; E11; E12; E44; G01; G18; G20; G21; 330; global financial crisis; Hyman Minsky; financial reform; Basel III; capital development; banks